SHARIA-COMPLIANT STOCKS AND MARKET RESILIENCE: EVIDENCE FROM THE 2025–2026 CORRECTION OF THE INDONESIA COMPOSITE INDEX - Angga Syahputra; Said Ramadhan (Journal on Islamic Economics, Finance & Banking [Z-CONOMICS], 2026)
This study examines the resilience of Sharia-compliant equities during the 2025–2026 correction of the Indonesian stock market. The research aims to analyse whether Sharia-compliant stocks demonstrate greater stability and resistance to market turbulence compared with conventional equities. Employing a quantitative comparative approach, the study focuses on the performance of the Indonesia Sharia Stock Index (ISSI) and Jakarta Islamic Index 70 (JII70) relative to the Indonesia Composite Index (IHSG) during a period characterised by heightened market uncertainty, global monetary tightening, geopolitical tensions, and volatile investor sentiment. The analysis is based on the concepts of market resilience, volatility, downside risk, and recovery performance. The findings indicate that Sharia-compliant equities possess structural characteristics that potentially enhance their resilience during market corrections. Lower leverage, restrictions on speculative activities, and stronger links to real economic sectors contribute to reduced downside exposure and relatively greater stability under adverse market conditions. Although Sharia-compliant stocks remain affected by macroeconomic and global market shocks, they appear to demonstrate stronger defensive characteristics and recovery capacity than conventional equities. The study contributes to the growing literature on Islamic capital markets by providing evidence on the role of Sharia screening in promoting financial resilience. The findings also offer practical implications for investors, regulators, and policymakers in strengthening sustainable and resilient investment strategies within the Indonesian capital market.